Psychological perspectives on juvenile homicide - Jaynes, Chae M. (The Routledge international handbook of juvenile homicide, 2024)
This chapter provides an overview of the major psychological perspectives in the field of criminology and their application to juvenile homicide offenders (JHOs). These perspectives include (1) rational choice and deterrence theories; (2) temporal orientation theories; (3) personality trait theories; and (4) other theories focused on cognitive function. Although little research has been conducted to test the applicability of these theories specifically to juvenile homicide, the existing research on delinquency and violence more broadly suggests these theories are applicable. However, there is a further need to assess the validity of these theories within a juvenile homicide context and evaluate whether there are important nuances associated with age and offense type. The chapter also discusses directions for future research for those interested in applying the most prominent psychological perspectives to the area of juvenile homicide.